Institute of Metals Division - The Atomic Volumes of Silicon, Germanium and Tin (TN) - T. Yoshioka; Paul A. Beck (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1965)
SILICON, germanium, and tin occur with both the white tine-type structure and the diamond cubic structure. In the latter form these elements are semiconductors; in the former they are metallic. The metallic form of germanium and silicon is obtained only under high pressure.' For all three elements the transition from the semiconductor to the metallic state is accompanied by a decrease in the atomic volume of somewhat more than 20 pctily2 Table I. At such a large compression the widening of the s and p bands is sufficient to make the energy gap of 1.1 ev, or less, of the semiconductor disappear, giving rise to the metallic state.*